Frontiers of empire : Max Sering, inner colonization, and the German East, 1871-1945 - Nelson, Robert L. 1971- (Cambridge University Press, 2024)
"How did the homesteads and reservations of the prairies of western North America influence German colonization, ethnic cleansing, and genocide in Eastern Europe? Max Sering, a world-famous agrarian settlement expert, stood on the Great Plains in 1883 and saw Germany's future in Eastern Europe: a grand scheme of frontier settlement. Sering was a key figure in the evolution of Germany's relationship with its eastern frontier, as well as in the overall transformation of the German Right from the Bismarckian 1880s to the Hitlerian 1930s. 'Inner colonization' was the settlement of farmers in threatened borderland areas within the nation's boundaries. Focusing on this phenomenon, Frontiers of Empire complicates the standard thesis of separation between the colonizing country and the colonized space and blurs the typical boundaries between colonizer and colonized subjects"--Page i